The Importance of Ethnically and Racially Underrepresented Faculty in Creating a Sense of Belonging for Black Students in Speech-Language Pathology. - Roberson-Middleton, Erica; Lee-Holloway, Shanna Caprice; Jocelyn, Jessica (Perspectives of the ASHA Special Interest Groups, 2026)
Purpose: In higher education, there remains a scarcity of ethnically and racially underrepresented faculty. The National Center for Education Statistics reported that there were 1.5 million full-time faculty at colleges and universities in the United States. Approximately 74% of full-time faculty were White, and 26% were faculty of color. Compared to these national statistics, there is even less (approximately 16%) racial and ethnic diversity among speech-language pathology faculty. Method: Through a comprehensive literature review and drawing from personal experiences of speech-language pathology faculty members from ethnically and racially underrepresented groups, the article aims to shed light on connections between ethnically and racially underrepresented faculty members' presence and engagement in communication sciences and disorders programs and Black students' recruitment and retention. Conclusion: Speech-language pathology academic leadership teams should intentionally allocate their current resources to not only prepare students for a diverse world but also prepare academic training programs to attract and sustain racially and ethnically diverse students and future clinicians.